2016
DOI: 10.1016/j.bjorl.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Complications of otitis media – a potentially lethal problem still present

Abstract: ICCs of OM, although uncommon, still occur. These cases require expensive, complex and long-term inpatient treatment and frequently result in hearing loss, neurological sequelae and mortality. It is important to be aware of this potentiality in children with COM, especially, and maintain a high index of suspicion in order to refer for otologic specialty care before such complications occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 36 publications
(32 reference statements)
1
24
0
7
Order By: Relevance
“…Worldwide, the incidence of acute otitis media is 10.85%, accounting for over 709 million new cases every year . It is associated with several acute complications and long‐term sequelae, which include hearing loss, delayed speech and neurologic development, tinnitus, and dizziness . In the past years, several studies have hypothesized the presence of high‐frequency hearing loss as a potential long‐term sequela of acute otitis media .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Worldwide, the incidence of acute otitis media is 10.85%, accounting for over 709 million new cases every year . It is associated with several acute complications and long‐term sequelae, which include hearing loss, delayed speech and neurologic development, tinnitus, and dizziness . In the past years, several studies have hypothesized the presence of high‐frequency hearing loss as a potential long‐term sequela of acute otitis media .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies aiming to evaluate patients who had recurrent acute otitis media or chronic otitis media with effusion using standard audiograms (250 Hz–8 kHz) failed to demonstrate significant threshold changes as compared with controls . However, studies using extended high‐frequency audiometry (8 kHz–16 kHz) reported downward threshold shifts in patients who had a history of recurrent acute otitis media.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been known that maxillary sinusitis [15] and otitis media [19] can cause intracranial infection. A recent report noted that 80 % of intracranial complications were secondary to chronic otitis media of which the incidence of intracranial complication was 0.8 %; 20 % were due to acute otitis media [20]. This reveals that otitis media causing intracranial infection often lack acute symptoms as well as odontogenic foci.…”
Section: Discussionmentioning
confidence: 94%